Changes in omentin levels and its mRNA expression in epicardial adipose tissue in patients undergoing elective cardiac surgery: the influence of type 2 diabetes and coronary heart disease - Matloch, Z; Kratochvílová, H; Cinkajzlová, A; Lipš, M; Kopecký, P; Pořízka, M; Haluzíková, D; Lindner, J; Mráz, M; Kloučková, J; Lacinová, Z; Haluzík, M (Physiological research, 2018)
Omentin is a protein produced by numerous tissues including adipose tissue. Its concentrations are decreased in patients with obesity, type 2 diabetes mellitus (DM) and coronary artery disease (CAD). Experimental studies suggest that omentin may have anti-inflammatory and insulin-sensitizing properties. In the present study, we measured circulating omentin levels and its mRNA expression in epicardial and subcutaneous fat, intercostal and heart muscle before and after elective cardiac surgery in patients with CAD (CAD+, DM-, n=18), combination of CAD and DM (CAD+, DM+, n=9) or with none of these conditions (CAD-, DM-, n=11). The groups did not differ in baseline anthropometric and biochemical characteristics with the exception of higher blood glucose and HBA(1c) in CAD+, DM+ group. Baseline circulating omentin levels tended to be lower in CAD+, DM- and CAD+, DM+ groups as compared to CAD-, DM- group and cardiac surgery increased its concentration only in CAD-, DM- group. The change in serum omentin levels during surgery inversely correlated with epicardial fat thickness. While baseline omentin mRNA expression did not differ among the groups in any of the studied tissues, its increase after surgery was present only in subcutaneous fat in CAD-, DM- and CAD+, DM- groups, but not in CAD+, DM+ group. Intercostal muscle omentin mRNA expression increased after surgery only in CAD-, DM- group. In conclusion, cardiac surgery differentially affects omentin levels and subcutaneous fat and skeletal muscle mRNA expression in patients without coronary artery disease and diabetes as compared to patients with these conditions.
Keywords: senioři; messenger RNA; nemoci koronárních tepen; cytokiny; Middle Aged; mužské pohlaví; Diabetes Mellitus, Type 2; GPI-Linked Proteins; Pericardium; Adult; Cytokines; elektivní chirurgické výkony; Elective Surgical Procedures; diabetes mellitus 2. typu; GPI-vázané proteiny; Coronary Artery Disease; ženské pohlaví; Gene Expression; lektiny; Lectins; Humans; RNA, Messenger; biologické markery; Adipose Tissue; lidé středního věku; exprese genu; dospělí; perikard; Biomarkers; Female; Aged; tuková tkáň; lidé; Male